An infant with refractory cytomegalovirus‐induced thrombocytopenia - Suguru Uemura (Clinical Case Reports, 2020)
Abstract The present case underscores the importance of considering the association of severe thrombocytopenia or immune thrombocytopenia with cytomegalovirus (CMV) infection because CMV‐induced thrombocytopenia occasionally requires antiviral therapy.